Utility of immature granulocyte in severity of helicobacter pylori infection - Serkan Sengul; Mehmet Kubat; Yilmaz Guler; Hasan Calis; Zulfikar Karabulut (Wolters Kluwer Medknow Publications, 2022)
Introduction: Helicobacter pylori infection is a chronic bacterial infection associated with some extragastric diseases as well as gastric involvements that occur most commonly worldwide. In our study, we aimed to investigate the usability of immature granulocytes as a basic indicator that can reflect the severity of helicobacter pylori inflammation, to the best of our knowledge, for the first time. Materials and Methods: Patients who underwent upper gastrointestinal endoscopy between April 2019 and April 2020 and were diagnosed with antral gastritis were included in this study. The relationship between helicobacter infection and its severity detected in gastric biopsies of patients and immature granulocyte count (IGC), immature granulocyte percentage (IG%), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and mean platelet volume (MPV) were investigated. Results: Of the 868 patients, 210 were HP negative, 658 were HP positive (218 mild HP positive, 293 moderate HP positive, and 147 severe HP positive). There were statistically significant differences between the HP negative and HP positive groups in terms of IGC, IG%, NLR, and PLR. However, IG% and IGC were not clinically useful because the median IG% (0.3 vs 0.3) and IGC (0.02 vs 0.02) were the same in the HP negative and total HP positive groups. Conclusion: In our study, IGC and IG% were not found useful to detect H. pylori intensity and severity of inflammation.